Characterization of a Novel Sequence Type (ST) 6758 Klebsiella Pneumoniae and the Role of IncX3 Plasmid in the Transmission of blaNDM - Zhang Y; Li Q; Li L; Guo H; He F (Infection and Drug Resistance)
Yawen Zhang,* Qiao Li,* Lirong Li, Hao Guo, Fang He Laboratory Medicine Center, Department of Clinical Laboratory, Zhejiang Provincial People’s Hospital (Affiliated People’s Hospital), Hangzhou Medical College, Hangzhou, Zhejiang, 310014, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fang He, Email hetrue@163.comPurpose: Carbapenem-resistant Klebsiella pneumoniae (CRKP) has emerged as a significant public health threat, particularly as a superbug responsible for nosocomial infections. In this study, we report a novel sequence type 6758 of K. pneumoniae harboring the blaNDM-1 gene.Material and Methods: Antimicrobial susceptibility testing was conducted according to the guidelines of the Clinical and Laboratory Standards Institute (CLSI). The complete genome sequence of the strain was determined using the Illumina NovaSeq 6000 platform and long-read MinION sequencer. Genomic features and resistance mechanisms of the strain were further comprehensively analysed using various bioinformatics approaches.Results: Antimicrobial susceptibility testing revealed that this strain exhibited resistance to multiple antimicrobials, including ceftazidime, ceftriaxone, cefazolin, cefepime, imipenem, meropenem, ampicillin/sulbactam, and sulfamethoxazole/trimethoprim. The genome analysis identified sixteen resistance genes. The blaNDM-1 carbapenemase gene is located on a 47,823 bp IncX3-type plasmid (pNDM-CRKP331). A total of 41 K. pneumoniae strains carrying similar IncX3-type plasmids were retrieved from the NCBI database, representing 20 sequence types (STs) across 11 countries. The most common resistance gene carried by these IncX3-type plasmids is blaNDM, and all these plasmids contain only the blaNDM gene. The blaNDM-carrying IncX3-type plasmids are widely prevalent in K. pneumoniae in China, spanning 15 STs.Conclusion: In summary, our study reports the first genome sequence of an ST 6758 K. pneumoniae strain containing the class B β-lactamase blaNDM-1 isolated from a clinical sample. Given the global emergence of blaNDM, measures should be taken to prevent the spread of these blaNDM-carrying IncX3-type plasmids. Our findings contribute to the understanding of the transmission mechanisms of blaNDM in K. pneumoniae.Keywords: carbapenem-resistant Klebsiella pneumoniae, blaNDM-1, whole-genome sequencing, IncX3 type plasmid, ST6758